Flipped Classroom Learning Model Using a Digital Self-Learning Network Infrastructure Administration - Reza Daryl Fiqri; C. Rudy Prihantoro; Lipur Sugiyanta (PT. Anagata Sembagi Education, 2024)
The flipped classroom model has emerged as a significant pedagogical innovation, offering an alternative approach to traditional teaching methods. This model is particularly relevant for vocational education, where practical skills and active learning are critical. Network Infrastructure Administration, a core subject in vocational high schools (SMKs), presents unique teaching challenges that can be addressed through this model. This study aims to develop and evaluate a flipped classroom learning model integrated with a digital self-learning and diagnostic system for vocational high schools' Network Infrastructure Administration course. A mixed-method research design was employed, involving quantitative and qualitative data collection. The study was conducted in several vocational high schools, with participants including teachers and students of the Network Infrastructure Administration course. Tools used included digital self-learning modules and a diagnostic system to continuously assess student performance and provide feedback. The implementation of the flipped classroom model with digital tools resulted in improved student engagement and learning outcomes. Quantitative data showed a significant increase in test scores and practical skill proficiency. Qualitative feedback from both teachers and students indicated higher satisfaction and motivation levels. The developed flipped classroom model, supported by a digital self-learning and diagnostic system, enhances the learning experience and effectiveness of teaching Network Infrastructure Administration in vocational high schools. These findings suggest that integrating technology with innovative pedagogical approaches can significantly improve vocational education. Future research should explore the long-term impact of this model and its applicability to other vocational subjects.